Capillaria spp. in a Reticulated Python (Python reticulatus) in Banyuwangi Reptile Community - Dini, Sayyida Kamila; Triakoso, Nusdianto; Saputro, Amung Logam; Yudhana, Aditya (Universitas Airlangga, 2022)
Reptiles as exotic pets become more commonly desired by society, one of which is the reticulated python. Pythons kept as pets also have a risk of disease infection including helminthiasis. Worm parasite infects snake by the oral route. Some snake feed including frogs and mice can act as an intermediate host for worm parasites. A male reticulated python was kept by a member of the Banyuwangi reptile community and was presented with healthy and normal eating habits. This case study was to determine the worm parasite in the wild-caught reticulated python kept as an exotic pet. Fresh fecal samples were stored in a container with 70% alcohol added as a preservative. The sample was then evaluated in the laboratory and examined using the native method, floatation method, and simple sedimentation method. As result, under the microscope to be the Capillaria spp. the egg was observed.